Nano-Medicine in the Cardiovascular System - Pretorius, Danielle; Serpooshan, Vahid; Zhang, Jianyi (Frontiers in Pharmacology, 2021)
Nano-medicines that include nanoparticles, nanocomposites, small molecules, and exosomes represent new viable sources for future therapies for the dysfunction of cardiovascular system, as well as the other important organ systems. Nanomaterials possess special properties such as their intrinsic physiochemical properties, surface energy and surface topographies which enhance advantageous cellular responses within the cardiovascular system, making them exceptionally valuable in future clinical translation applications. Successful translation of nano-medicines into appropriate cardiovascular applications requires a comprehensive understanding of both nanomaterials and biomedicine. In this review, we highlight some of the major types of nano-medicine systems that are currently being explored in the cardiac field. This review focusses on the major differences between the systems, and how these differences affect the specific therapeutic or diagnostic applications. The important concerns relevant to cardiovascular nano-medicines, such as cellular responses, toxicity of nanomaterials, as well as cardio-protective and regenerative capabilities are discussed. This review provides an overview of the current development of nano-medicines specific to the cardiovascular system, discussing the diverse nature and applications of nanomaterials as therapeutic and diagnostic agents.